Heat transfer and exergy loss in cut out conical turbulators - Durmus, A (Pergamon-Elsevier Science Ltd, 2004)
It would be misleading to consider only the construction costs of heat exchangers in their design because high service costs during their service life may also greatly increase total costs. Therefore, energy saving aspects are very important in the design, construction and operation of the heat exchangers. For this reason, various active or passive methods have been sought to save energy by increasing the heat transfer coefficients in the cold and warm fluid sides in the heat exchangers. In this study, the effect of cut out conical turbulators, placed in a heat exchanger tube at constant outer surface temperature, on the heat transfer rates was investigated. The air was passed through the exchanger tube, the outer surface of which was heated with saturated water vapor. The experiments were conducted for air flow rates in the range of 15,000 less than or equal to Re less than or equal to 60,000. Heat transfer, pressure loss and exergy analyses were made for the conditions with and without turbulators and compared to each other. Some empirical correlations expressing the results were also derived and discussed. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: turbulators; concentric heat exchanger; exergy loss; NTU